Experimental field test on a multipiece steel wheel and influence of the material properties on its fatigue life evaluation. (May 2022) - Mazzoni, Alberto; Solazzi, Luigi
Highlights: Field tests are important to understand real load conditions on industrial wheels. Material characteristic are fundamental for the fatigue life estimation of wheels. Strain gauge data and material parameters can be used for random fatigue analysis. Overload in service can lead to crack development and failure on industrial wheels. Improvement in fatigue life of wheels using steel S690 instead of S355 is assessed. Abstract: Wheels are important components for the general vehicle reliability. Their design validation is usually based on fatigue tests conducted in laboratory under constant amplitude load conditions, according to industrial standards. In the off-highway industry, the variety of applications and machines often makes it difficult to complete standard tests, due to the high load capacity requirements or to lack of information about specific applications. Therefore, strain data acquisition during field test on real machines can be a useful tool to understand actual load conditions. In this paper, a fatigue life assessment based on field test is applied to a multipiece wheel that experienced an unexpected crack development in a critical section. The local strain approach is used, together with rainflow counting method and Palmgren-Miner rule for the total damage evaluation. Mean stress influence is considered through the Smith-Watson-Topper method. The fatigue life estimation is completed for structural steel S355J2. The influence of extremely hard working conditions is also investigated and assessed to be the root cause of the failure. Finally, a possible design improvement regarding the use of a higher base material grade S690 is evaluated and proposed.